Upaya Meningkatkan Perancangan Pembelajaran Di Sekolah Dasar denganImplementasi Model Perkuliahan Cooperatif Learning - ikippgrisemarang, Mudzanatun, S.Pd., M.Pd.2; ikippgrisemarang, Iin Purnamasari, S.Pd., M.Pd.3 (MALIH PEDDAS, 2011)
ABSTRAK Â Upaya Meningkatkan Perancangan Pembelajaran Di Sekolah Dasar denganImplementasi Model Perkuliahan Cooperatif Learning Â Education serves to develop skills and form the character and civilization of the nations dignity in the framework of the nations intellectual life (UU no. 20 in 2003). While the purpose of education according to UU No. 20 in 2003 for the development of potential learners in order to become a man faithful and devoted to God Almighty, noble, healthy, knowledgeable, capable, creative, independent, and become democratic citizens and accountable. Elementary school teachers have a status as a classroom teacher. Classroom teacher will teach a range of subjects. Because a variety of lesson, teachers will prepare to teach a variety of forms decidedly. Learning math is not the same as learning science, social studies, or the Indonesian language. This has prompted researchers to conduct this discussion. Based on the background, the formulation of the problem in this study are (1) How PGSD lectures in according to the students? (2) How the students design learning in primary schools by implementing cooperative learning? This research use an approach of Research and Development (R & D) described by Borg and Gall (2003: 571) to adapt. Research will be conducted over four months. Place-making research data in S1 Studies Teacher Education Program Elementary School (PGSD) IKIP PGRI Semarang Jalan Lontar No.1, Semarang. Locations were chosen on PGSD because the students will become elementary school teachers. So, this is a precise object as a field of research. Efforts to improve the skill of making lesson plans on four semesters to regular students is to practice making lesson plans. freshman make 50% correct learning porpose for the work of RPP I. This data was obtained from a sample of 10% students of class 4A, 4C, 4D, 4E, and 4F. The result of RPP II data analysis which has satisfied increase is the model selection but it still need a special attention for the learning porpose formulation. Development of indicators with C1, 2, 3, Affective and Psychomotor also not satisfactory. Making questions with three question types is good, making LKS is good enough. Based on that data it can be concluded that the manufacture of RPP can increase due to implementation of the model learning. However, this research is still necessary advice for the perfect RPP creation for Students PGSD. The suggestions can be submitted are (1) Expand the indicators pulled exercise with multiple domains (2) formulate goals with the right condition. (3) Improving the writing worksheets that conditionate the process of finding something on the students.